Processing, characterisation and oxidation resistance of βNiAl bond coat: Al and Zr effects - Chandio A.D.; Shaikh A.A.; Salman W.; Ahmed H. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Platinum-modified-βNiAl is a bond coat (BC) material for thermal barrier coatings (TBCs) applications applied on aeroengine hardware to reduce their surface temperatures. However, it is desirable to minimize its production and material costs by the low-cost alternatives of similar performance. It has been acknowledged that the small concentration of the reactive elements (REs), such as Zr, Hf, and Y, could tremendously enhance the oxide adhesion even in some cases better than Pt modified counterparts. The aim of this study was to design and fabricate the Zr-modified-βNiAl bond coat on CMSX-4 superalloy using an aluminizing method. Moreover, the study focused on the development of a systematic understanding of underlying mechanisms behind the beneficial effects of REs. Initially, three sets of BCs were prepared: Zr-free βNiAl (undoped), Al and Zr co-deposited in a single-step process (1SP), and Zr and Al, which were individually deposited in two processing steps (2SP): zirconizing and aluminizing. Such three sets of BCs helped to understand the processing, as well as Zr and Al effects on scale adhesion. In particular, 1SP/2SP BCs showed uniformity of Zr in the form of precipitates and networks that caused hardness enhancement. All BCs were isothermally oxidized at 1150°C for 100 hours wherein 2SP revealed the best spallation resistance, microstructural stability, and its Zr-oxide pegs were extended to substrates. In addition to the Zr effect, BC Al content was found to affect the oxide adhesion equally. Under identical Zr contents (of 1SP and 2SP = 1at %), the higher Al showed the better spallation resistance while lower Al caused the inverse effect of Zr owing to its reactive nature that was termed as over doping. Moreover, it was established that over-doping either local or into entire BC, accelerated the Al depletion that destabilized the βNiAl into γ’-Ni3Al phase. An extensive discussion is presented in the light of the observed results.